Soil-derived Streptomyces sp. GMR22 producing antibiofilm activity against Candida albicans: bioassay, untargeted LC-HRMS, and gene cluster analysis - Nirwati, Hera; Damayanti, Ema; Sholikhah, Eti Nurwening; Mustofa, Mustofa; Widada, Jaka (Elsevier Ltd, 2022)
Biofilm-forming fungi, Candida albicans, are currently a serious problem in infectious disease cases. Soil bacteria Streptomyces sp. GMR22 have a large genome size and antifungal metabolites against C. albicans, but its potential antibiofilm activity is not clearly defined. The aims of this study were to determine the antibiofilm activity of GMR22 against C. albicans, identify the main constituents of active extracts, and investigate the biosynthesis gene clusters encoding the enzymes related to metabolism pathways. Antifungal and antibiofilm measurements were performed using in vitro assays on C. albicans ATCC 10231. Main constituents of active extracts were analyzed using untargeted Liquid Chromatography tandem High-Resolution Mass Spectrometry (LC-HRMS). RAST software was applied to investigate the gene clusters of the biosynthesis pathways based on whole genome sequences. Chloroform extract of GMR22 has antifungal and antibiofilm properties at 13–420 μg/mL with palmitic acid (C16H32O2, 273.27028 Da), a saturated fatty acid as a major constituent (42.74). Streptomyces sp. GMR22 has 53 subsystems related to fatty acids biosynthesis (Fab) FAS II. The Kyoto Encyclopedia of Gene and Genome map of Fab revealed 10 of 21 (47.6%) gene clusters encode enzymes related to Fab. There were six gene clusters encoding the enzymes related to the hexadecenoic acid (palmitic acid) biosynthesis pathways: 6.4.12; FabD, FabH, FabF, FabG, FabI and 1.14.192. Each enzyme was encoded by 3–14 genes. These results confirmed that soil Streptomyces sp. GMR22 bacterium has remarkable biotechnological potential by producing fatty acids which are mostly palmitic acid as an active antibiofilm agent against C. albicans.